PENGARUH STRUKTUR KEPEMILIKAN SAHAM TERHADAP BIAYA AUDIT - Cintya Anindita; Abdul Rohman (Diponegoro Journal of Accounting, 2021)
The purpose of this study is to analyze empirically the effect of corporate ownership structure and audit fees paid to external auditors. Independent variable of this analysis is corporate ownership structure which is divided into three type, namely managerial ownership structure, foreign ownership structure, and goverment ownership structure, the dependent variable of this analysis is audit fees paid to external auditors.The sample of this research is non-financial companies listed on Bursa Efek Indonesia (BEI) from 2017 to 2019. This study applies purposive sampling method to sampling the population. Based on the specified criteria in the puposive sampling method, total sample used ini this research was 261 companies. Hypothesis testing used in this study is multiple linear regression analysis. The results from testing the hypothesis is the corporate ownership structure has a relationship with audit fees. The managerial ownership structure has a significant negative relationship on audit fees. The foreign ownership structure has a significant positive relationship on audit fees.the goverment ownership structure has a significant positive relationship on audit fees.